Isolated Fibular Stress Fractures: Demographic and Radiographic Factors. Issue 4 (16th October 2019) - Sarpong, Nana O.; Levitsky, Matthew; Held, Michael; Greisberg, Justin K.; Vosseller, J. Turner
Category: Ankle, Trauma Introduction/Purpose: Fibular stress fractures are rare injuries that are incompletely understood in terms of pathogenesis and predisposing factors. While stress fractures all involve relative stress concentration in a finite area leading to local mechanical failure, the risk factors for this injury have not been assessed. Their relative rarity has made understanding of these risk factors difficult. In a retrospective case series, we sought to define demographic and radiographic risk factors for isolated fibular stress fractures. Methods: We retrospectively reviewed the records of 13 patients with isolated fibular stress fractures at our institution between January 2010 and November 2018. We collected and analyzed baseline demographic data and radiographic parameters including prior history of fracture, location of stress fracture, bone quality, and heel alignment. Results: The cohort consisted of 6 men and 7 women with a mean age of 41.8 years at the time of diagnosis of the fibular stress fracture. The average BMI in the cohort was 28.5 kg/m2. The location of the stress fracture was in the distal third of the fibula in 69.2% (9/13), proximal third in 23.1% (3/13), and middle third in 7.7% (1/13). There was no evidence of osteopenia on radiographic analysis in any patients, by assessment of the senior author and attending radiologist at our institution. Isolated stress fractures in the distal third of the fibula were observed more commonly in women. Distal fibula stress fractures were associated with physiologic hindfoot valgus, while proximal fractures were seen with a varus hindfoot. Conclusion: In this retrospective case series of a rare injury, isolated stress fractures in the distal third of the fibula were the most common fibular stress fracture. Proximal fibular stress fractures were associated with a varus hindfoot. All fractures in this case series healed with immobilization in a walking boot with or without a short period of nonweightbearing.